Sex-stratified and age-adjusted social gradients in tobacco in Argentina and Uruguay: evidence from the Global Adult Tobacco Survey (GATS). Issue 6 (1st July 2014) - De Maio, F G; Konfino, J; Ondarsuhu, D; Goldberg, L; Linetzky, B; Ferrante, D
Abstract : Objective: To examine social gradients in tobacco use in Argentina and Uruguay, using newly available directly comparable data sets. Methods: Secondary analysis of Global Adult Tobacco Survey data from Argentina (N=6645) and Uruguay (N=5581). Social gradients in current tobacco use, exposure to secondhand smoke, and cessation attempt were examined with sex-stratified and age-adjusted logistic regression. Results: Among men, there is evidence of higher odds of being a current smoker among respondents with lower levels of education, but the association is only statistically significant for respondents with less than primary education in Uruguay (OR=2.15, 95% CI 1.22 to 3.77). Similarly, women with lower levels of education have higher odds of being a current smoker in Uruguay. The association between education and exposure to secondhand smoke is broadly similar for both sexes in both countries, with generally higher odds among groups with low education, though the relationship is only statistically significant among men in Uruguay (OR=1.77, 95% CI 1.08 to 2.92). In both countries, respondents with lower levels of education in general have higher odds of having attempted to quit smoking in the past year, although these associations did not attain statistical significance. Conclusions: Social gradients in tobacco use, exposure to secondhand smoke and cessation attempts are broadly similar in both countries. Efforts to evaluate the long-term effects of tobacco control efforts in these countries should monitor how policies affect national averages, and the social gradients that are embedded in aggregate data.